Analysis of standards of quality for outcomes in acute heart failure patients directly discharged home from emergency departments and their relationship with the emergency department direct discharge rate. Issue 3 (March 2021) - Miró, Òscar; López-Díez, María Pilar; Rossello, Xavier; Gil, Víctor; Herrero, Pablo; Jacob, Javier; Llorens, Pere; Escoda, Rosa; Aguiló, Sira; Alquézar, Aitor; Tost, Josep; Valero, Amparo; et al.
Highlights: The study checked the level of achievement of defined quality standards for outcomes. The Spanish emergency departments (ED) are quite far from fulfilling these proposed standards. Experts recommended direct discharge for EDs able to observe acute heart failure patients should be over 40%. Only 12% of Spanish EDs achieve the 40% of direct discharge. High percentages of direct discharge from ED negatively impact revisit or hospitalization but not mortality. Abstract: Objective: Experts recommended that direct discharge without hospitalization (DDWH) for emergency departments (EDs) able to observe acute heart failure (AHF) patients should be >40%, and these discharged patients should fulfil the following outcome standards: 30-day all-cause mortality <2% (outcome A); 7-day ED revisit due to AHF < 10% (outcome B); and 30-day ED revisit/hospitalization due to AHF < 20% (outcome C). We investigated these outcomes in a nationwide cohort and their relationship with the ED DDWH percentage. Methods: We analyzed the EAHFE registry (includes about 15% of Spanish EDs), calculated DDWH percentage of each ED, and A/B/C outcomes of DDWH patients, overall and in each individual ED. Relationship between ED DDWH and outcomes was assessed by linear and quadratic regression models, non-weighted and weighted by DDWH patients provided by each ED. Results: Among 17, 420 patients, 4488 had DDWH (25.8%, median ED stay = 0 days, IQR = 0–1). Only 12.9% EDs achieved DDWH > 40%. Considering DDWH patients altogether, outcomes A/C were above the recommended standards (4.3%/29.4%), while outcome B was nearly met (B = 10.1%). When analyzing individual EDs, 58.1% of them achieved the outcome B standard, while outcomes A/C standards were barely achieved (19.3%/9.7%). We observed clinically relevant linear/quadratic relationships between higher DDWH and worse outcomes B (weighted R 2 = 0.184/0.322) and C (weighted R 2 = 0.430/0.624), but not with outcome A (weighted R 2 = 0.002/0.022). Conclusions: The EDs of this nationwide cohort do not fulfil the standards for AHF patients with DDWH. High DDWH rates negatively impact ED revisit or hospitalization but not mortality. This may represent an opportunity for improvement in better selecting patients for early ED discharge and in ensuring early follow-up after ED discharge.